Nonuniformities in the angle of repose and packing fraction of large heaps of particles - Topic, Nikola; Gallas, Jason; Pöschel, Thorsten (Physical Review Letters, 2012)
We report a numerical investigation of the structural properties of very large three-dimensional heaps of particles produced by ballistic deposition from extended circular dropping areas. Very large heaps are found to contain three new geometrical characteristics not observed before: they may have two external angles of repose, an internal angle of repose, and four distinct packing fraction (density) regions. Such characteristics are shown to be directly correlated with the size of the dropping zone. In addition, we also describe how noise during the deposition affects the final heap structure. © 2012 American Physical Society.